Empirical Findings on Business–Society Relations in Europe - Konrad, A. (Journal of business ethics, 2006)
Based on a theoretical exploration in a previous article, this paper empirically analyzes which issues of SD are taken into account by corporations and stakeholders in what way, and to what extent the concept of sustainable development (SD) can be achieved through stakeholder relations management (SRM) on the corporate level. An important basis for this empirical analysis is a referential framework, which specifies 14 issues of SD. In a first empirical step, the literature-based framework has been operationalized for the business world by analyzing sustainability reports. In a second empirical step, the operationalized framework served as the basis for a survey of selected MNCs. The analyses of the sustainability reports and the survey show how MNCs deal with particular issues of SD and what role they perceive particular stakeholders play. A key conclusion of the article is that SRM indeed promotes SD, but that it is no alternative to predictable government regulation.